Improving Hydrogen Sensing Performance of TiO2 Nanotube Arrays by ZnO Modification - Yu, Aihua; Xun, Haitao; Yi, Jianxin (Frontiers in Materials, 2019)
In this work, anodization was utilized to synthesize highly ordered TiO2 nanotube arrays, and ZnO was successfully decorated onto the surface of as-prepared TiO2 nanotubes via a facile impregnation method. The gas sensing performance of TiO2@ZnO composite was systematically studied. At a working temperature of 300 °C, the response of TiO2@ZnO to 100 ppm H2 was ~340, 2.7 times larger than that of pristine TiO2. A power-law relationship between the response and H2 concentration was observed. In addition, the response time was significantly reduced by four times, and improved selectivity to H2 was achieved. The highly improved sensing performance of TiO2 nanotubes by ZnO decoration may be attributed to the enhanced oxygen adsorption and formation of n-n heterojunctions.